Alteration of select gene expression patterns in individuals infected with HIV‐1. Issue 4 (30th January 2014) - Serrao, Erik; Wang, Chia‐Hao; Frederick, Toinette; Lee, Chi‐Lin; Anthony, Patricia; Arribas‐Layton, David; Baker, Kerry; Millstein, Joshua; Kovacs, Andrea; Neamati, Nouri
<x xml:space="preserve">Abstract</x> Multiple human proteins have been shown to both support and restrict viral replication, and confirmation of virus‐associated changes in the expression of these genes is relevant for future therapeutic efforts. In this study a well‐characterized panel of 49 individuals either infected with HIV‐1 or uninfected was compiled and analyzed for the effect of HIV infection status, viral load, and antiretroviral treatment on specific gene expression. mRNA was extracted and reverse transcribed from purified CD4+ cells, and quantitative real‐time PCR was utilized to scrutinize differences in the expression of four host genes that have been demonstrated to either stimulate (HSP90 and LEDGF/p75) or restrict (p21/WAF1 and APOBEC3G) proviral integration. HIV infection status was associated with slight to moderate alterations in the expression of all four genes. After adjusting for age, mRNA expression levels of HSP90, LEDGF/p75 and APOBEC3G were found to all be decreased in infected patients compared to healthy controls by 1.43‐, 1.26‐, and 4.71‐fold, respectively, while p21/WAF1 expression was increased 2.35‐fold. Furthermore, individuals receiving raltegravir exhibited a 1.28‐fold reduction in LEDGF/p75 compared to those on non‐raltegravir antiretroviral treatment. Identification of these and similar HIV‐induced changes in gene expression may be valuable for delineating the extent of host cell molecular mechanisms stimulating viral replication. J. Med. Virol. 86:678–686, 2014. © 2014 Wiley Periodicals, Inc.